Association of MC4R, FABP3 and DGAT1 gene polymorphisms with reproductive traits in two domestic pig lines - Gondim, V. S. [UNESP]; Soares, J. S.; Lugo, N. A.H. [UNESP]; Stafuzza, N. B. [UNESP]; Vieira, G. S.; Aspilcueta-Borquis, R. R. [UNESP]; Pascoal, L. A.F.; Silveira, A. C.P.; Tonhati, H. [UNESP]; Antunes, R. C. (Genetics and Molecular Research, 2019)
MC4R, FABP3 and DGAT1 are important genes related to productive and reproductive traits in pigs, such as food intake, growth rate, back fat thickness reduction and lactation. Selection of pigs for lean meat production may lead to losses in reproductive charcters because reduction of backfat thickness and low feed intake during the lactation phase can affect reproduction. To examine this possibility, we evaluated possible associations of SNPs in the MC4R (SNPg.1,578C>T), FABP3 (SNPg.240T>C) and DGAT1 (SNPg.9,422C>T) genes with the number of weaned piglets, birth weight, total weight of litter at birth, total litter weight at weaning, age at first mating and parity interval in 227 animals of two maternal lines: European and European/Chinese pigs. Specific fragments of the genes under study were amplified by Multiplex ARMS-PCR and genotyped in an automatic sequencer. SNPs in the MC4R (SNPg.1,578C>T) and FABP3 (SNPg-240T>C) genes showed three genotypic variations in both lines, while the SNP (SNPg.9,422C>T) of the DGAT1 gene had three genotypic variations in European swine and two genotypic variations (homozygotes) in the European/Chinese breed. Polymorphisms of MC4R, FABP3 and DGAT1 genes evaluated by variance analysis had significant associations with the reproductive traits age at first mating and parity interval, while only the DGAT1 gene in the European line was significantly associated with the production traits mean weight at weaning and total litter weight at birth andnd weaning.
Keywords: Genetic association; Genotyping; Maternal line; SNPs; Sus scrofa domesticus